2022
DOI: 10.1021/acsaem.2c02949
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ceria on the Oxygen Reduction Activity and Thermal Cycling Stability of BaCo0.4Fe0.4Zr0.1Y0.1O3−δ Cathode for Solid Oxide Fuel Cells

Abstract: BaCo0.4Fe0.4Zr0.1Y0.1O3−δ (BCFZY) has been demonstrated to be a highly active yet large thermal expansion cathode catalyst for solid oxide fuel cells (SOFCs). In this work, gadolinia doped ceria (GDC) was mixed with BCFZY (BCFZY-GDC) to investigate its oxygen reduction reaction activities and chemical/thermal compatibility with electrolyte. Improved thermal compatibility of BCFZY-GDC with electrolyte and cathodic activity in symmetric cells were obtained, while, in contrast to the results of the common composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…S4 , both samples revealed infrared absorption peaks corresponding to in the range of 3200–3700 cm −1 after complete hydration (3% H 2 O-air for 150 h). Similar phenomena have been observed in other perovskite air electrode materials, such as BaCo 0.7 Fe 0.2 Zr 0.1 O 3−δ [ 45 ] and BaCo 0.7 Ce 0.24 Y 0.06 O 3−δ [ 46 ]. The absorption peak in D-SFN is more pronounced than in SFN, indicating enhanced hydration capabilities.…”
Section: Resultssupporting
confidence: 83%
“…S4 , both samples revealed infrared absorption peaks corresponding to in the range of 3200–3700 cm −1 after complete hydration (3% H 2 O-air for 150 h). Similar phenomena have been observed in other perovskite air electrode materials, such as BaCo 0.7 Fe 0.2 Zr 0.1 O 3−δ [ 45 ] and BaCo 0.7 Ce 0.24 Y 0.06 O 3−δ [ 46 ]. The absorption peak in D-SFN is more pronounced than in SFN, indicating enhanced hydration capabilities.…”
Section: Resultssupporting
confidence: 83%
“…Specifically, the n = 0.735−0.965 for LF confirms that it may be related to the gas diffusion processes within the porous electrode; the n = 0.263−0.757 for IF indicates that it corresponds to the transfer of O 2− at the electrode/electrolyte boundary, while n = 0.129−0.027 for HF evidences that this process is associated with the charge transfer. 42,43 In addition, n values of the three cathode materials in the whole ORR reaction process are calculated in Figure S9. It was found that the ORR rate-limiting steps of the three cathode materials under different P O2 values were mainly caused by oxygen dissociation and charge transfer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To overcome this rate-limiting step, developing a triple conducting electrode is considered as an effective approach to extend active reaction sites throughout the entire electrode surface and interface for accelerating the kinetics of oxygen evolution and proton transfer. [20][21][22][23] There have been several examples of triple conducting oxide (TCO) materials being developed, demonstrating significant proton conductivity and improved cell performance by increasing the reaction efficiency of both the hydrogen oxidation reaction (HOR) and the oxygen reduction reaction (ORR) at triple phase boundaries (TPBs). [24][25][26][27] PrBa 0.5 Sr 0.5 Co 2Àx Fe x O 5+d (x = 0, 0.5 and 1.0), one promising layered perovskite, was compounded to promote electrochemical active sites, realizing lower area specific resistance (ASR), 0.33 O cm 2 at 500 1C and 0.056 O cm 2 at 600 1C, than Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-d at similar temperature (0.70 O cm 2 at 500 1C).…”
Section: Introductionmentioning
confidence: 99%